A study of loneliness associated with depression level among geriatrics at nursing homes in territory of Klang valley / Amirul Farizi Jamaluddin - Jamaluddin, Amirul Farizi (2012)
This thesis reported on a cross-sectional survey that investigated loneliness associated with depression level among geriatrics at nursing homes. Administration of two questionnaires to explore participant‟s knowledge were used to examine the depression level among geriatrics and how it is associated with their loneliness, since most of geriatrics at nursing homes are homeless and some are being abandoned by their own family. Nursing homes in Klang Valley were selected as samples of this thesis. This chapter briefly describes the context of study, the purpose and significance of the study as well as the study question. It concludes with a discussion on the organization of this thesis.